The impact of the 1991 cholera epidemic on the north coast of Peru - Centeno Ramos, Joana (2022)
At the end of January 1991, cholera made its appearance in the Peruvian territory. Chancay, Chimbote and Piura were simultaneously affected. These initial foci unleashed an epidemic that managed to spread throughout the country and then to South America. It is proposed to evaluate the sanitary and environmental factors for their implications in the expansion of cholera. Likewise, the relationship of climatic changes such as the El Niño phenomenon and the appalling conditions of the Peruvian health system are highlighted